Working Capital Management, Firm Performance: A Case Study of Listed Firms on MAI - Wanganusorn, Bhannawat; Tulasombat, Sirikul; Bangmek, Ratchaneeya; Awirothananon, Thatphong (Hatyai Academic Journal, 2025)
This study investigates the relationship between working capital management and firm performance within the Market for Alternative Investment (MAI) in Thailand. By utilizing panel data analysis, the study examines how different working capital policies and the efficiency of working capital management affect the firm performance of listed companies. The population for this study comprises 210 companies listed on the Market for Alternative Investment, spanning across eight industry sectors. Using a purposive sampling method, a sample of 199 companies was selected, resulting in 2,295 observations covering 14 years from 2009 to 2022. The findings reveal that working capital policy significantly affects firm performance. Specifically, an aggressive working capital investment policy enhances performance by minimizing excess inventory and associated costs, while a conservative working capital financing policy improves performance by mitigating liquidity issues. The efficiency of working capital management, as measured by the cash conversion cycle, is negatively related to firm performance, although its impact is minor compared to the cash ratio. The performance index shows no significant impact on firm performance. These insights underscore the importance of strategic WCM in enhancing firm value and operational efficiency.